Current clinical presentations of AIDS dementia in a tropical environment: study of 26 observations in the neurology department of the University Hospital of Conakry - Mohamed Lamine Touré; Foksouna Sakadi; Mamady Mory Keita; Guelngar Carlos Othon; Souleymane M’bara Diallo; Thierno Hamidou Baldé; Francois Dago Kassa; Bademba Diallo; Mandandi Hinima; Mariama Boubacar Diallo; Sanny Yaya Aminou; Namory Camara; et al. (European Journal of Medical Research, 2023)
Abstract Introduction In sub-Saharan Africa (SSA), the clinical and progressive diagnostic certainty of AIDS dementia is difficult to establish due to under-medicalization and delays in consultation and especially the diversity of etiologies of demented states. Material and methods We carried out a retrospective study of 196 patients hospitalized for dementia syndrome between 2016 and 2021 in the neurology department of the University Hospital of Conakry. The criteria labeled in this study are those retained by the DSM-IV and the classification of the American Academy of Neurology (AAN) developed in accordance with the WHO. Results HIV etiology was identified in patients aged 44–67 years (17 women and 19 men). The clinical picture was dominated by severe cognitive disorders, slowed ideation, memory disorders and reduced motor skills associated with personality changes. Neurological examination revealed dysphoric disorders in most patients, sphincter abnormalities in 13 cases and labio-lingual tremor in 11 cases. Diagnosis was based on positive serological tests for HIV1 antibodies (25 cases) and HIV2 antibodies (1 case) using the Elisa and Western blot techniques, and the presence of discretely hypercellular CSF. Magnetic resonance imaging contributed to the diagnosis, showing diffuse white matter abnormalities with hyper signals on T2-weighted or FLAIR sequences. Conclusion This study shows a non-stereotype clinical picture of AIDS dementia requiring a differential diagnosis with other infectious dementias. These results are important for the therapeutic and prognostic discussion.